Reliability Centered Maintenance Method on Quotient Gradient System (QGS) in Production at PT ABC Dumai - Melliana, M (Journal of Economics and Management Scienties, 2024)
QGS A1 is a powerful crusher and dryer designed based on reference drying equipment with good performance efficiency. QGS A1 has a very important function in expediting the production process, but this tool often breaks down so it really affects the smooth production. In connection with the damage to the tool needs to be examined to find out what maintenance should be done.This study aims to find out earlier the damage that affects the smooth production so that it can be known what maintenance actions must be carried out . This study uses the Reliability Centered Maintenance method which utilizes information on reliability and weaknesses as well as maintenance actions to choose from. The results of this study found a solution that the QGS A1 treatment run to failure was 81.2%, direct condition was 18.18%, and failure finding was 0%. The conclusion of this study is Condition Directed, namely the actions taken aim to detect damage by visual inspection, checking tools and monitoring a number of existing data.